2020
DOI: 10.1071/an18537
|View full text |Cite
|
Sign up to set email alerts
|

Grazed chicory, plantain or ryegrass–white clover alters milk yield and fatty acid composition of late-lactating dairy cows

Abstract: The aim of the present research was to compare milk fatty acid composition of cows grazing perennial ryegrass–white clover pasture (RGWC), with that of cows grazing alternative forages of chicory or plantain. Fifty-four cows, balanced for milk solids, days in milk and bodyweight, were divided evenly into replicated groups of six cows/group. Cows grazing chicory or plantain had similar estimated dry-matter intake (17.7 kg DM/cow.day) and milk-solid (MS) yield (1.93 kg MS/cow.day), which were greater (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
6
13
1
Order By: Relevance
“…This is the second study in a series of experiments investigating the effect of high moisture forages on the production and quality of milk and associated environmental impacts in pastoral dairy systems. Our first proof-of-concept study showed that under pastoral grazing feeding high moisture, herb diets altered milk FA composition without affecting production [19]. The results of the present study confirm the positive effect of feeding CH on PUFA and demonstrate that producers can influence FA composition through changes in feeding regimes.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is the second study in a series of experiments investigating the effect of high moisture forages on the production and quality of milk and associated environmental impacts in pastoral dairy systems. Our first proof-of-concept study showed that under pastoral grazing feeding high moisture, herb diets altered milk FA composition without affecting production [19]. The results of the present study confirm the positive effect of feeding CH on PUFA and demonstrate that producers can influence FA composition through changes in feeding regimes.…”
Section: Discussionsupporting
confidence: 80%
“…It is interesting that feeding reproductive CH at 55-58% of the diet of mid lactating dairy cows increased milk production compared to the control-feeding regime, a result similar to previous findings when CH was fed while vegetative [19,20]. Muir et al [30], on the other hand, did not observe any differences in milk production between the control ryegrass and reproductive CH at 50% of the diet in summer.…”
Section: Milk Production and Rumen Fermentationsupporting
confidence: 83%
See 2 more Smart Citations
“…However, Wang et al (2015) noticed, in insect herbivores feeding on plantain, an increase in IG did not reduce intake rate but lowered growth rate, leading to the suggestion that PSM reduce the efficiency of nutrient utilisation. Interestingly, a similar effect has occasionally been observed in dairy cows grazing plantain or grass-clover pastures as a control, whereby greater apparent intake was measured for plantain but milk production was similar to the control (Box et al 2017b;Mangwe et al 2018). The theory that PSM may alter intake and nutrient use efficiency has been explored in greater detail for phenolics such as condensed tannins which will be addressed later in this review.…”
Section: Plant Secondary Metabolitesmentioning
confidence: 63%